New findings of the family Pardaliscidae from the southwestern Atlantic: the genus Halicoides Walker, 1896 - Nascimento, Priscila S. Do; Serejo, Cristiana S. (Zootaxa, 2024)
Halicoides is a diverse genus of Pardaliscid previously known from the Atlantic Ocean (North and SE), and the Pacific Ocean (SW and NE). This is the first record of Halicoides from off the Brazilian coast, SW Atlantic Ocean. Samples were collected with box core and/or van veen grabs between Espírito Santo, Campos and Santos Basins (19º–26º S), from shallow waters to deep-sea depths (29–3084 m), expanding the world bathymetry of the genus. Two new species is herein described, Halicoides campensis sp. nov., which differs from all Halicoides species by combination of characters as: gnathopod 1, carpus and propodus with sparse setae; pereopods 3–4, merus and carpus strongly robust; urosomite 2 with dorsal tooth tiny, but distinguishable; uropod 3, outer ramus bi-articulated with small article 2 about 10% the length of the ramus; and Halicoides iemanja sp. nov., which can be distinguished by antenna 1, primary flagellum with many long aesthetascs; pereopods 3–4, merus and carpus weakly expanded; urosomite 2 dorsally smooth; pereopod 5, dactylus as long as the propodus; uropod 3, outer ramus biarticulated with article 2 about 18% the length of the ramus. Based on the species described herein, the diagnosis of the genus is modified and a world key for all 14 known Halicoides species is provided. The present study is an effort in understanding and unrevealing the macrofauna from the Brazilian margin bringing new data on the family Pardaliscidae that was found in a wide bathymetric range of the Campos, Santos and Espírito Santo Basins.